Influence of Gas Washing and Oil Mixing on the Phase Behavior and Physical Properties of Cambrian Light Oils in the Tazhong Uplift, Tarim Basin - Chengsheng Chen; Yifeng Wang; Zhihua He; Jian Li; Yunpeng Wang (Energies)
Gas washing and oil mixing have been widely studied in the Tazhong area of the Tarim Basin, but their effects on Cambrian subsaltic dolomite reservoirs have not yet been adequately explored. In this study, the influence of gas washing and oil mixing on light oils from these reservoirs was investigated. Using n-alkane mass depletion (Q value) analysis, light oils from wells ZS1 and ZS5 were analyzed to quantify the intensity of gas washing and to identify possible oil mixing in the Cambrian Awataga (Є2a) and Wusongar (Є1w) reservoirs. Unaltered light oil was recovered and models of phase behavior were constructed by PVT simulation and basin modeling to compare with altered light oils. The results show that the light oil in well ZS1 experienced medium-strength gas washing (Q value = 40.88%), while the gas washing in well ZS5 was weaker (Q value < 40.88%), providing evidence of oil mixing. Despite these changes, the light oils in the Cambrian reservoirs maintained a single liquid-phase state over geologic time without transitioning to condensate or gas phases. These results improve the understanding of gas washing in the Tazhong area and show that it has significantly altered the Cambrian reservoirs and affected the preservation of hydrocarbons after oil accumulation.